Femtosecond laser programmed artificial musculoskeletal systems - Ma, Zhuo-Chen; Zhang, Yong-Lai; Han, Bing; Hu, Xin-Yu; Li, Chun-He; Chen, Qi-Dai; Sun, Hong-Bo (Nature communications, 2020)
Natural musculoskeletal systems have been widely recognized as an advanced robotic model for designing robust yet flexible microbots. However, the development of artificial musculoskeletal systems at micro-nanoscale currently remains a big challenge, since it requires precise assembly of two or more materials of distinct properties into complex 3D micro/nanostructures. In this study, we report femtosecond laser programmed artificial musculoskeletal systems for prototyping 3D microbots, using relatively stiff SU-8 as the skeleton and pH-responsive protein (bovine serum albumin, BSA) as the smart muscle. To realize the programmable integration of the two materials into a 3D configuration, a successive on-chip two-photon polymerization (TPP) strategy that enables structuring two photosensitive materials sequentially within a predesigned configuration was proposed. As a proof-of-concept, we demonstrate a pH-responsive spider microbot and a 3D smart micro-gripper that enables controllable grabbing and releasing. Our strategy provides a universal protocol for directly printing 3D microbots composed of multiple materials. Musculoskeletal systems are recognized as a model for designing robust yet flexible microbots but the development of artificial musculoskeletal systems at nanoscale currently remains challenging. Here the authors report a laser programmed artificial musculoskeletal systems for prototyping 3D microbots, using relatively stiff SU-8 as the skeleton and pH-responsive proteins as the smart muscle.